Offshore Technology Conference 1988
DOI: 10.4043/5621-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rock Mechanics Of The Ekofisk Reservoir In The Evaluation Of Subsidence

Abstract: The subsidence occurring in the Ekofisk field originates from the compaction of the reservoir rock due to the increasing stress placed upon it as reservoir pressure is reduced with production from the field. The mechanical properties of the reservoir rock determine how much compaction will take place for given conditions in the field and are therefore a key factor in determining the degree to which subsidence will occur. These mechanical properties can be combined with other reservoi r informati on (pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…7 shows PV reduction vs. applied isostatic stress and elapsed time for a sample from another prospect, Prospect B. (Similar transient creep has also been observed in chalks, 5 mary creep, there also exists steady-state creep and tertiary creep. See Ref.…”
Section: Pv Behaviormentioning
confidence: 56%
“…7 shows PV reduction vs. applied isostatic stress and elapsed time for a sample from another prospect, Prospect B. (Similar transient creep has also been observed in chalks, 5 mary creep, there also exists steady-state creep and tertiary creep. See Ref.…”
Section: Pv Behaviormentioning
confidence: 56%
“…With the aid of a finite element analysis Gambolati et al (1999a) proved that under the effect of a pressure drawdown ∆p the reservoir deforms as if it were confined within a natural oedometer subject to an effective vertical stress increase equal to ∆p. This was already noticed 10 years earlier by Johnson et al (1989) who observed (p. 171) that "A large ratio of lateral extent to vertical thickness…means that the compaction will occur largely in the vertical direction with minimal horizontal displacements. Tests Downloaded by [Northeastern University] at 04:58 21 November 2014 to simulate compaction in the subsurface should be confined tests that prevent the rock from undergoing any lateral deformation".…”
Section: Mechanics Of Reservoir Compaction and Migration To The Grounmentioning
confidence: 61%
“…Generally, c M is considered to be the most representative parameter for the correct description of the in situ compaction of sedimentary rocks and hence for the most realistic prediction of the related land subsidence (Johnson et al, 1989;Ruddy et al, 1989). Recent numerical results by Gambolati et al (1999) provide further evidence that the loaded sediments in the reservoir deform following an oedometric path.…”
Section: Structural Modelmentioning
confidence: 99%